Physical Properties and Sound Absorption Performance of Durian (Durio spp.) Peel-Based Particleboard with Cold-Water Soaking and Density Variation - Dina Setyawati; Nurhaida; Catherine Priscilla Buulolo (Green Insight Solutions, 2026)
Durian (Durio spp.) peel waste has potential as a lignocellulosic raw material, offering a sustainable pathway for wood-based panel production and acoustic applications. This study evaluates the effects of board density and cold-water soaking pretreatment on the physical properties and sound absorption performance of particleboard manufactured from durian peel particles. Boards were produced at target densities of 0.40 and 0.50 g/cm³ using 15% urea–formaldehyde adhesive, with particle soaking durations of 0, 12, and 24 h. Physical properties were assessed according to JIS A 5908, while acoustic performance was measured using a two-microphone impedance tube across 64–6400 Hz. Results showed that board density significantly influenced moisture content, thickness swelling, and acoustic behavior, whereas cold-water soaking primarily affected dimensional stability and water absorption. Lower-density boards exhibited higher sound absorption due to increased porosity, with the highest absorption coefficient (α = 0.87) obtained at 0.40 g/cm³ after 12 h cold-water soaking at 3150 Hz. All panels met JIS requirements for density, moisture content, and thickness swelling. Sound absorption was generally greater at medium to high frequencies, while higher-density boards demonstrated improved sound insulation but reduced absorption efficiency. According to the ISO classification, the panels ranged from class D to class B, indicating sound absorption capabilities from normal to high. These findings demonstrate that durian peel–based particleboard can serve as a viable, sustainable material for interior acoustic applications while supporting efficient biomass utilization.